COST-VOLUME-PROFIT CALCULATION ANALYSIS AS A PROFIT PLANNING APPROACH IN “MARKISA MANIS MAMPANG” MICRO BUSINESS DEPOK CITY, WEST JAVA PROVINCE - Dyah Mieta Setyawati; Susanti Usman; Feny Fidyah (Jurnal Ekonomi, 2023)
Analysis of the calculation of Cost-Volume-Profit (CVP) aims to identify problems related to sales at the business planning stage using the Contribution Margin, Break-Even Point (BEP), Margin of Safety (MOS), Degree of Operating Leverage (DOL) and planning approaches. profits targeted by business actors. The research method used is a quantitative descriptive method. The data used is primary data in the form of business reports "Markisa Manis Mampang" for the months September, October and November 2022. Data analysis uses five CVP calculation formulas. The results of the research show that unit sales have a contribution to cover fixed costs and generate operating profit. The business achieves a BEP of IDR 1,549,948 or when product sales reach 155 units within three months; the MOS value as the budgeted sales security limit has a maximum decrease and does not suffer a loss of IDR 3,928,552 or 71.71% ; The DOL value shows that every 1% increase in sales revenue will result in a 1.39% increase in net profit. Profit planning to achieve a targeted profit of 15% in the next 3 months will occur if sales of passion fruit juice products have reached 607 units or in rupiah sales amounting to IDR 6,070,000